Advanced Glycation End Product Formation in Human Cerebral Cortex Increases With Alzheimer-Type Neuropathologic Changes but Is Not Independently Associated With Dementia in a Population-Derived Aging Brain Cohort. Issue 9 (7th August 2020) - Chambers, Annabelle; Bury, Joanna J; Minett, Thais; Richardson, Connor D; Brayne, Carol; Ince, Paul G; Shaw, Pamela J; Garwood, Claire J; Heath, Paul R; Simpson, Julie E; Matthews, Fiona E; Wharton, Stephen B
Abstract: Diabetes mellitus is a risk factor for dementia, and nonenzymatic glycosylation of macromolecules results in formation of advanced glycation end-products (AGEs). We determined the variation in AGE formation in brains from the Cognitive Function and Ageing Study population-representative neuropathology cohort. AGEs were measured on temporal neocortex by enzyme-linked immunosorbent assay (ELISA) and cell-type specific expression on neurons, astrocytes and endothelium was detected by immunohistochemistry and assessed semiquantitatively. Fifteen percent of the cohort had self-reported diabetes, which was not significantly associated with dementia status at death or neuropathology measures. AGEs were expressed on neurons, astrocytes and endothelium and overall expression showed a positively skewed distribution in the population. AGE measures were not significantly associated with dementia. AGE measured by ELISA increased with Consortium to Establish a Registry for Alzheimer's Disease (CERAD) neurofibrillary tangle score (p = 0.03) and Thal Aβ phase (p = 0.04), while AGE expression on neurons (and astrocytes), detected immunohistochemically, increased with increasing Braak tangle stage (p < 0.001), CERAD tangle score (p = 0.002), and neuritic plaques (p = 0.01). Measures of AGE did not show significant associations with cerebral amyloid angiopathy, microinfarcts or neuroinflammation. In conclusion, AGE expression increases with Alzheimer's neuropathology, particular later stages but is not independently associated with dementia. AGE formation is likely to be important for impaired brain cell function in aging and Alzheimer's.